Kualitas Produk, Harga dan Word Of Mouth Terhadap Minat Beli Konsumen (Studi Empiris Pada Produk Minuman Minyum Di Outlet Jalan Besar Tanjung Anom Medan) - Muhammad Umar Maya Putra; Nur’Ainun Nur’Ainun; Sri Nur Ningsih; Syafrida Damanik (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2023)
The purpose of this study was to analyze the effect of product quality, price and word of mouth on consumer buying interest in drinking beverage products. The sample of this research is consumers who buy Beverage products as many as 96 samples. The data used is primary one. The statistical method used is multiple linear regression analysis with a quantitative approach using the classical assumption test first. The results of this study indicate that partially the variable Product Quality (X1) has a positive and significant effect on Purchase Intention (Y), indicated by a t-count of 2.041 > t-table of 1.98609 with a significance of 0.008 <0.05. Partially Price (X2) has a positive and significant effect on Purchase Intention (Y), indicated by a t-count of 3.009 > t-table of 1.98609 with a significance of 0.006 <0.05. Partially Word of Mouth (WOM (X3) has a positive and significant effect on Purchase Intention (Y), indicated by a t-count of 2.696 > t-table of 1.98609 with a significance of 0.008 <0.05. While simultaneously both Product Quality (X1), Price (X2) and Word of Mouth (X3) have a positive and significant effect on Purchase Intention with a F-count of 9.739 > F-table of 2.70 with a significance of 0.002 <0.05. The Recommendation for the Owner has to improve the quality of the product itself by promoting in the social media frequently